Continuous degradation of a mixture of sulfonamides by Trametes versicolor and identification of metabolites from sulfapyridine and sulfathiazole - Rodríguez Rodríguez, Carlos E. (2012)
In this study, we assessed the degradation ofthe sulfonamides sulfapyridine (SPY) and sulfathiazole (STZ) by the white-rotfungus Trametes versicolor. Complete degradation was accomplished in fungal cultures at initial pollutant concentrations of approximately 10 mg L−1, although a longer period of time was needed to completely remove STZ in comparison to SPY. When cytochrome P450 inhibitors were added to the fungal cultures, STZ degradation was partially suppressed, while no additional effect was observed for SPY. Experiments with purified laccase and laccase mediators caused the removal of greater than 75% of each antibiotic. Ultra-performance liquid chromatography-quadupole time of flight mass spectrometry (UPLC-QqTOF-MS) analyses allowed the identification of a total of eight degradation intermediates of SPY in both the in vivo and the laccase experiments, being its desulfonated moiety the commonly detected product. For STZ, a total of five products were identified. A fluidized bed reactor with T. versicolor pellets degraded a mixture of sulfonamides (SPY, STZ and sulfamethazine, SMZ) by greater than 94% each at a hydraulic residence time of 72 h. Because wastewater contains many diverse pollutants, these results highlight the potential of T. versicolor as a bioremediation agent not only for the removal of antibiotics but also for the elimination of a wide range of contaminants.